The Communication Language Style of The Government of Kuwait During The Covid-19 Pandemic | Gaya Bahasa Komunikasi Pemerintah Kuwait di Masa Pandemi Covid-19 - Ghufron, Zaki; Anwar, Endang Saeful; Alawiyyah, Azizah; Mufrodi, Mufrodi (Ta’lim al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
The purpose of this study is to describe that the Government of Kuwait, through its official social media, uses a lot of euphemistic and dysphemic language styles in conveying information in the era of the Covid-19 pandemic. This study uses a qualitative approach with content analysis to understand the symbolic messages contained in documents, paintings, dances, songs, literary works, and others as unstructured data. The data collection technique used is the observation and note-taking technique. Listening in the context of this study means reading, which is then recorded to document the data obtained. The data analysis technique used is the equivalent referential technique to find out grammatical units such as euphemisms and dysphemisms, while to analyze the background of the use of euphemisms and dysphemisms, pragmatic equivalent analysis is used. Based on the results of an analysis of data obtained from the official social media of the Ministry of Health of Kuwait, many euphemistic and dysphemistic forms were found in conveying information regarding the latest matters and developments regarding Covid-19 in the country of Kuwait. It is used for specific purposes. The purpose of using euphemistic forms is to avoid mentioning negative reality, which aims to minimize the harmful effects of utterances that seem scary, worrying, make noise, offend, hurt, disrespect, or violate social norms. Euphemistic forms also aim to evoke an optimistic attitude toward residents in dealing with the coronavirus pandemic. The use of the dysphemistic form used by the Kuwaiti Ministry of Health in presenting information about matters related to Covid-19 in that country is aimed at scaring, showing annoyance, and giving warnings so that they are even more vigilant in dealing with the Covid 19 pandemic.